A Voltage Control Strategy of VSG Based on Self-Adaptive Inertia Coefficient and Droop Coefficient. (26th April 2021) - Lin, Shizhi; Lin, Lei; Wen, Buying
Abstract : With the increasing penetration rate of distributed renewable energy in power systems, the control strategy of virtual synchronous generator (VSG) is widely used for several years. Some existing VSG control strategies have been able to solve the stability problems caused by the abnormal grid voltage, but the effects of the inertia coefficient and the droop coefficient on the voltage stability are not taken into account. In order to further improve the voltage stability of the microgrid system, a voltage control strategy of VSG based on self-adaptive inertia coefficient and droop coefficient is proposed in this paper. When the voltage is far from the steady state, the increase of the inertia coefficient can decrease the voltage deviation. On the contrary, when it is close to the steady state, the decrease of the inertia coefficient can make the system response speed accelerate. According to the real-time voltage deviation, the droop coefficient can change adaptively to decrease the adjusting time and the voltage deviation during the disturbance. Finally, the simulation model of VSG is built by MATLAB/Simulink for conducting simulation experiments. Compared with other strategies, the correctness and effectiveness of the proposed control strategy are validated.